African American Women's Perceptions of Cardiovascular Disease After Myocardial Infarction: A Phenomenological Inquiry. Issue 6 (November 2019) - Jones, Loretta; Williams, Susan; Bydalek, Kathryn; Elkins, Casey; Fruh, Sharon
Abstract : Background: The primary cause of death among African American women older than 50 years is cardiovascular disease. Cardiovascular disease affects more than 16.8 million Americans and occurs when plaque builds up in the arteries that provide blood to the heart. This often leads to a partial or complete blockage, causing a myocardial infarction (heart attack). There is limited research regarding the lived experiences of African American women before and after a myocardial infarction. Objective: The purpose of this qualitative study was to explore the experiences of African American women living in the southern region of the United States who have experienced a myocardial infarction. Methods: A hermeneutic phenomenological framework guided the study. Semistructured, audiotaped interviews were conducted to elicit narratives from 7 participants. Interview data were transcribed verbatim and then coded and analyzed using Colaizzi's phenomenological analysis framework. Results: The findings revealed 6 major themes: life before myocardial infarction, causes of my myocardial infarction, myocardial infarction warning signs, life after myocardial infarction, cardiac rehabilitation, and family support. Lifestyle changes must be implemented to prevent a second blockage. Attending cardiac rehabilitation and incorporating regular physical exercise are recommended to help prevent further heart damage and to improve quality of life.